(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents a comprehensive analysis of the morphofunctional indicators of Greco-Roman wrestlers across different age groups. Based on anthropometric and functional characteristics, criteria for athlete preparation have been developed. The study examined indicators of athletes aged 7 to 17, such as body weight, body length, arm and leg length, chest circumference, and vital lung capacity. Based on the results obtained, model-based recommendations were developed corresponding to the wrestlers’ age and body constitution. These recommendations are scientifically substantiated and play an important role in optimizing athletes’ technical and tactical training.